PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN. 026 SIARANG ARANG KECAMATAN PUJUD KABUPATEN ROKAN HILIR - Parulian Harahap Parulian Harahap; Zairul Antosa Zariul Antosa; Damanhuri Daud Damanhur Daud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problem this research is the students achievement of social studies SD Negeri 026 Siarangarang fourth graders still low with an average value of 62 and minimum completeness criteria (KKM) social studies is 67. Between students, amounting to 20 people only 45%, this research is Classroom Action Research (CAR), which aims to improve the student achievement of social studies class IV at SD Negeri 026 Siarangarang with implementation incuiri. Formulation of the problem : is the implementation incuirios social students can improve students achievement of social studies at SD Negeri 026 Siarangarang. The research was conducted on Maret 03, 2014 to April 07, 2014 by 2 cycles. Subjects were students of SD Negeri 026 Siarangarang, totaling 20 people who use the data source. The data collection instruments in this thesis is a teacher and students activities sheets an students achievement. This thesis presents the results obtained each day before the action an improve in base score cycle with the average being 62. In the first cycle improve an average of 69 and an improve in the second with an average of 81. Activities of the teacher in the learning process in cycle of 84%, with increase big as 89% and the second meeting improve 94% and the second meeting improve 100%. Results of data analysis of students activities in the fisrt cycle with the fisrt meeting of an average of 40,80% and a second meeting improve to 71,20% and a second meeting improve to 87,20% at the first meeting of the second cycle with an average of 98,40%. Resuts in the class IV SD Negeri 026 Siarangarang that the implementsation of incuiri of social students can improve student achievement of social studies at fourth graders SD Negeri 026 Siarangarang. Keywords: Model Cooferative Learning snowball throwing of social students